Agrifood systems: Transformation, structural change, and development - Diao, Xinshen; McMillan, Margaret S.; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2025)
Agricultural transformation has long been critical to improving access to food, reducing poverty, and stimulating economic growth, but the role of agriculture in structural change and economic development is evolving in the modern context. This chapter explains the shifting paradigms in our understanding and approaches to agricultural transformation, which continue to redefine discourse, research, and action.